Aircraft Pitch Control Design using Observer-State Feedback Control - Hanum Arrosida; Mohammad Erik Echsony (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2017)
Pitch is a movement of an aircraft achieved by tilting the elevator control which makes the nose of aircraft ascend or descend. This research will design a control system that controls the slope of the x-axis or pitch with the observer-state feedback to keep the aircraft always in the position setpoint, the stabilization of the pitch angle at the value of 0 radians. The applied controller is tested under three different conditions based on the variation of the gain value of Q and R that will affect the observed gain matrix (L gain) and the matrix state-feedback gain (K gain). The variation with the gain value of Q = 10 and R = 0.1 is the best result of the three kinds of testing performed with the fastest stabilization processing time, that is 7 seconds, to reach a steady state condition and the minimum pitch angle deviation value is 0.08 radians. The use of the observer has a significant influence on the pitch angle deviation of the aircraft. When using the observer, the pitch angle deviation value is 0.08 radians, and 0.2 radians without the observer. The larger result of pitch deviation angle will affect the stability of the aircraft's motion and cause the slope of the movement on the x-axis become greater so that the aircraft is prone to fall.